UPAYA MENUMBUHKAN KESADARAN BERPERILAKU HIDUP BERSIH DAN SEHAT DI PULAU SABANGKO MELALUI SEMINAR PERSPEKTIF FIKIH LINGKUNGAN - Muhammad Iqbal; Muhammad Firdaus; Muhammad Rafli; Fauzan Bramantyo; Irsa Asrianti; Nur Adelia Fajrianti; Fauziah Adrianti Wahab; Sartika Dewi; Dewi; Andi Tunedianti (PPM LP2M UIN Alauddin Makassar, 2023)
Clean and healthy living behavior (PHBS) is a step that must be taken to achieve optimal health for everyone. In the sources of Islamic teachings, namely the Qur'an and al-Sunnah, it is explained that Islamic teachings highlight environmental cleanliness and health issues. This community service work program was carried out starting with a location survey on Sabangko Island, preparing a community empowerment plan in implementing religious values by means of FGD (Focus Group Discussion), carrying out socialization of the importance of clean and healthy living behavior to the community, youth leaders and students. female student at UPT SDN 41 Sabangko. In Environmental Jurisprudence, PHBS is defined as attitudes and actions to maintain the cleanliness of the body and the environment, and prevent the spread of disease in order to create healthy and comfortable environmental conditions. Apart from that, maintaining a clean environment is an obligation for every Muslim. This is in accordance with Islamic teachings which emphasize that the universe is a trust from Allah SWT. So, we as humans must care for and maintain it so that it remains sustainable. Islam is a religion that regulates all aspects, including how humans maintain environmental cleanliness. Clean and healthy living behavior (PHBS) is something that is highly emphasized in the Islamic religion.